CARACTERIZAÇÃO FÍSICO QUÍMICA DAS SEMENTES DE ARAÇÁ E POTENCIAL ANTIOXIDANTE DO ÓLEO DAS SEMENTES EM ÓLEO DE GIRASSOL INDUZIDO À OXIDAÇÃO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
The strawberry guava (Psidium cattleianum) is a class of fruits widely distributed in Brazilian territory showing different species. Although still little explored, studies have reported the presence of bioactive compounds in the composition of species by assigning to these fruits nutritional properties and functional interesting from a technological point of view. The objective of this work was to evaluate the proximate composition and the concentration of bioactive compounds (phenolic compounds and acid fítico) yellow strawberry guava (Psidium cattleianum var. Lucidum) and red strawberry guava (Psidium cattleianum Sabine). In addition to the percentage composition, were identified minerals of seeds by spectroscopy of atomic absorption. The oil of the seeds was characterized by physical-chemical analysis, spectroscopic and chromatographic and their antioxidant capacity was tested by DPPH method and subsequently evaluated in protection of sunflower oil subjected to foto-oxidação and termo-oxidação. The seeds were rich in nutrients and minerals, especially calcium (2329,76 mg/ 100g – red guava;2344,64 mg/100 g – yellow guava), potassium (1608,26 mg/ 100g – red guava; 1746,61 mg/ 100g – yellow guava), magnesium (832.09 mg/100 g – red guava; 946.6 mg/100 g – yellow guava) and sodium (573.26 mg/100 g – red guava; 448.25 mg/100 g – yellow guava). Was not detected the presence of phenolic compounds, but the seeds showed levels of expressive fitic acid (≈ 600 mg/100 g), an antioxidant potential used in the food industry. The oil of seeds presented good quality proven by low acidity level and peroxides, through the analysis of magnetic resonance and chromatography was detected large amounts of linoleic acid (≈ 74%) in its composition showing the predominance of unsaturated fatty acids. The DPPH method was efficient for determination of antioxidant activity and oil presented EC50 of 56.98 ug/mL and 51.01 ug/mL. The oil had good action as an antioxidant in protecting the sunflower oil subjected to oxidative stress, preventing the increase in the index of peroxides and free fatty acids and maintaining the integrity of oil. In general the seeds of strawberry guava of both species showed good characteristics and oil showed a composition interesting contributing to exploitation of our biodiversity.
Keywords: minerais; ácido fítico; oxidação; minerals; fitic acid; oxidation; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS